The Photocatalytic Application of Semiconductor Stibnite Nanostructure Synthesized via a Simple Microwave-Assisted Approach in Propylene Glycol for Degradation of Dye Pollutants and its Optical Property - Eksuree Saksornchai (2018)
© 2017, The Author(s). Stibnite (Sb 2 S 3 ) semiconducting material was successfully synthesized by a rapid and facile microwave route using antimony chloride (SbCl 3 ) and sodiumthiosulfate (Na 2 S 2 O 3 ) dissolved in propylene glycol (PG) containing different hydroxyethyl cellulose (HEC) masses. The phase identification, morphology, and elemental composition of products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), field- emission scanning electron microscopy (FE-SEM), energy dispersive X-ray (EDX) spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The results revealed the orthorhombic phase of Sb 2 S 3 single crystal-forming sheaf-like nanostructure, and a possible formation mechanism was proposed and discussed. Its direct band gap calculated from UV-visible absorption is 1.60 eV. In this research, the photocatalytic activities of Sb 2 S 3 nanostructure were investigated through the degradation of methyl orange (MO) and methylene blue (MB) under visible light irradiation. The as-obtained 0.30 g HEC-added solution (0.3 HEC-Sb 2 S 3 ) photocatalyst exhibited better photocatalytic activity than the other products, which degraded 91% of MO within 300 min and 90% of MB within 240 min under the Xe-lamp irradiation. The first-order plot was fitted with this experiment which the rate constant (k) of 0.3 HEC-Sb 2 S 3 for MO and MB degradation are 0.0085 and 0.0098 min −1 , respectively. Therefore, the new experience with a novel and simple synthetic procedure of Sb 2 S 3 photocatalyst that exhibits the characteristics of a highly effective photocatalyst under visible light irradiation was discovered.